Analysis and comparison of SOA, EDFA and RAMAN optical amplifiers - Moreno, Sergio; Torres, Daniel; Puerto, Gustavo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
In this document, the structure and operation of the optical amplifiers SOA, EDFA and Raman are exposed in a general way, in addition, a comparison between the optical technologies mentioned above is presented, where the fields of action of each one of them, and the advantages of hybrid models of optical amplification. Likewise, the issue of non-linearities and their contribution will be addressed.